Solid lipid nanoparticles for increased oral bioavailability of acalabrutinib in chronic lymphocytic leukaemia - Swagata Sinha; Punna Rao Ravi; Makarand Somvanshi; S. R. Rashmi (Discover Nano)
Abstract Acalabrutinib (ACP) is a first-line treatment for chronic lymphocytic leukemia but suffers from poor and variable oral bioavailability due to its pH-dependent solubility, CYP3A4 metabolism, and P-gp efflux. Thus, the objective of this study was to improve the solubility and dissolution behaviour, in turn enhancing bioavailability, by formulating solid lipid nanoparticles (SLNs). ACP loaded SLNs (ACP-SLNs) were prepared via solvent-free hot emulsification followed by a double sonication process. A combination of glyceryl di-behenate and stearyl palmitate along with Tween 80 was used as the lipid phase to dissolve ACP. A 1% w/v Poloxomer188 solution served as the aqueous phase. The optimized ACP-SLNs were spherical in shape and had particle size of 234.7–257.5 nm, PDI of 0.261–0.320 and loading efficiency of 18.70 ± 1.78%. A typical biphasic release pattern was observed from ACP-SLNs in the in vitro dissolution studies under gastrointestinal and plasma pH conditions (> 90% drug release at pH 4.5 ± 0.2, 6.8 ± 0.2 (representing GIT), and 7.4 ± 0.2 (representing plasma) at 8, 16 and 24 h, respectively). The freeze-dried product was stable when stored at 5 °C for over 6 months. Compared with the bulk drug suspension, the ACP-SLNs suspension resulted in 2.29-fold increase in oral bioavailability and more importantly 2.46-fold increase in the distribution of drug to spleen. Additionally, inhibition of lymph production and flow by administering cycloheximide resulted in 46.01% decrease in the overall absorption of ACP-SLNs, indicating the significance of lymphatic uptake process in the oral absorption of ACP-SLNs. Graphical Abstract